Transverse colon volvulus: A case report - Chambi-Torres, Javier Bernardo (2017)
A colon volvulus is the twisting of a colonic segment on its mesentery causing bowel obstruction. The transverse colon volvulus is an uncommon condition. We report the case of a 55-year-old male who initially showed bloating and abdominal pain, lack of bowel movements and flatus, nausea and hyporexia. During an exploratory laparotomy, a volvulus covering the transverse colon to the splenic flexure was found and resected with a posterior anastomosis of the transverse and descending colon. In conclusion, this clinical case report aims to show an uncommon case of colon volvulus and, at the same time, send the message that a colon volvulus is an acute (surgical) abdomen that medical personnel should know how to clinically recognize, because its immediate intervention will prevent the ischemia and subsequent necrosis of the large intestine.